Photocatalytic Conversion of Carbon Dioxide with Water into Methane: Platinum and Copper(I) Oxide Co‐catalysts with a Core–Shell Structure1. Issue 22 (22nd April 2013) - Zhai, Qingge; Xie, Shunji; Fan, Wenqing; Zhang, Qinghong; Wang, Yu; Deng, Weiping; Wang, Ye
<x xml:space="preserve">Abstract</x> Binary co‐catalysts of Pt and Cu2O with a core–shell structure significantly enhance the photocatalytic reduction of CO2 with H2O to CH4 and CO. The Cu2O shell provides sites for the preferential activation and conversion of CO2, whereas the Pt core extracts the photogenerated electrons from TiO2. The deposition of Cu2O shell on Pt nanoparticles markedly suppresses the reduction of H2O to H2 (see picture).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>